Analisis Kebutuhan Konsumen sebagai Pondasi Mutu dan Keunggulan Kompetitif Lembaga Pendidikan - Johan Wahyu Tri Astuti; Hariyanto Hariyanto (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
Analyzing consumer needs in education is a crucial strategic step to support competitiveness and educational quality. A deep understanding of consumer expectations and demands enables educational institutions to design relevant, adaptive, and high-quality programs to produce competent, globally competitive graduates. Analyzing consumer needs is crucial for educational institutions, as it serves as a basis for understanding the expectations and demands of students, parents, and the community. This analysis aims to adjust the curriculum, learning methods, and facilities to meet the actual needs of consumers. Consumer needs analysis also serves as a reference for improving service quality, competitiveness, and creating satisfaction for educational service users. This article analyzes consumer needs in improving the competitiveness and quality of educational institutions through library research. This research analyzes various previous studies, including relevant journals, books, and articles. The results of this study indicate that analyzing consumer needs is crucial in both education and business, including adapting services to expectations, increasing satisfaction and loyalty, improving quality and competitiveness, and anticipating changing trends. Educational institutions can use the QFD (Quality Function Deployment) strategy and the Kano method to analyze consumer needs. If educational institutions are able to accurately analyze consumer needs, learning programs can be designed to be more relevant and adaptive. This will improve the quality of education and the institution's competitiveness at both the local and global levels